The Technology of Ratings Then and Now; Hiding in Plain Sight. Issue 1 (19th January 2016) - Wilson, Berry K.; Donnellan, John T.
Abstract : The subprime crisis seriously undermined the credibility of the rating agencies and their approach to analyzing credit risk. Along with other identified problems with bond ratings, this study investigates the issue that the technology used by the ratings agencies is at best dated and little changed since John Moody published his first bond ratings in 1909. The study compares the predictive accuracy of Moody's bond ratings with the structural modeling approach of Vassalou and Xing (2004), using railroad data from the Great Depression. Study results show that the structural modeling approach outperforms the expert judgment incorporated in Moody's bond ratings from that period.